Review of Universal Human Rights Theory in the Perspective of Law and Justice - Misdin Arifin HM; Sabna Anggraini (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
This study analyzes the conceptual framework and philosophical foundations of human rights (HAM) through a review of key legal theories. The discussion begins with natural law theory, which argues that human rights are inherent, universal, and derived from transcendental ethical principles as a guide for positive law. As an antithesis, this study presents the theory of legal positivism, which emphasizes that human rights are a formal product of state institutions, where legal validity is separate from moral considerations. Next, this study examines theories of justice, particularly John Rawls's concept of